Synergistic effects of overexpression of BMP-2 and TGF-β3 on osteogenic differentiation of bone marrow mesenchymal stem cells - Wang, Yilin (Mol Med Rep, 2016)
Bone morphogenetic protein 2 (BMP-2) and transforming growth factor β (TGF-β) isoforms are important in advancing bone regeneration. The aim of the present study was to investigate the positive and reciprocal effect of TGF-β3, one of the three TGF-β isoforms, on BMP-2 in promoting osteogenic differentiation. Exogenous BMP-2 and TGF-β3 genes were separately, and in combination, overexpressed in rabbit bone marrow-derived mesenchymal stem cells (rBMSCs). Expression levels of BMP-2 and TGF-β3 were evaluated using reverse-transcription-polymerase chain reaction (RT-PCR) and Western blotting assays. Furthermore, the osteogenic differentiation capacities of BMSCs were assessed by measuring Alizarin Red S staining, an alkaline phosphatase activity assay, and quantification of the osteogenic-specific genes, Runt-related transcription factor 2 (Runx2) and Osterix (Osx). Using lentiviral-mediated transfection, robust co-transfection efficiency of >90% was achieved. RT-PCR and immunoblotting results indicated a marked elevated expression of BMP-2 and TGF-β3 in rBMSCs undergoing co-transfection, compared with transfection with BMP-2 or TGF-β3 alone, indicating that BMP-2 and TGF-β3 are synergistically expressed in rBMSCs. Furthermore, enhanced osteogenic differentiation was observed in rBMSCs co-transfected with BMP-2/TGF-β3. The present study successfully delivered BMP-2 together with TGF-β3 into rBMSCs with high efficiency for the first time. Furthermore, TGF-β3 overexpression was demonstrated to enhance the osteogenic efficacy of BMP-2 in rBMSCs, and vice versa. This provides a potential clinical therapeutic approach for regenerating the function of osseous tissue, and may present a promising strategy for bone defect healing.